Analysis of Poetic Personality- “Sarojini Naidu” Nightingale of India was a Poet and Politician” - Gulnaz Fatma; Nahla Pirzada; Sameena Begum; Saba Tarique (East Asian Journal of Multidisciplinary Research, 2023)
Sarojini Naidu was a student who excelled academically, a renowned freedom fight activist in India, and a poet who wrote sonnets. She is popularly known as the "Nightingale of India" and has been given this title for many years. She was the first lady to hold the position of President of India in our country, she was a notable person in Indian women's history, and she was the first Governor of Uttar Pradesh after the state of Uttar Pradesh gained its independence. She was one of the most well-known figures of the 20th century, and her presence on our planet as a powerful figure is celebrated annually on the holiday that is known as "Women's Day." The significant achievement that has been set in the field of poetry is the topic that will be discussed in this paper. Her sense of poetry is centered on an extraordinary bank of words that are so culturally specific that they can be sung with genuine feelings. In the year 1905, she had the poem "Bull Bule Hind" published; this was the beginning of her exploration into the literary realm. The Pardah Nashin, The Village Song, Lotus, and The Bird of Time are the primary focal the points of this paper's analysis.